Counsellor and Client Reliance on Verbal and Nonverbal Cues in Judging Competency, Trustworthiness, and Atractiveness - Lee, Dong Yul; McGill, Mary Ellen; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study was conducted to examine the degree to which clients and counsellors rely on verbal and nonverbal cues in judging certain personal attributes of each other. It was predicted that clients would rely more on nonverbal cues than on verbal cues in judging the competence, trustworthiness, and attractiveness of counsellors, whereas counsellors would rely more on verbal cues than on nonverbal cues in judging the same attributes in clients. Thirty-two counsellors conducted a 20-minute interview with 32 clients. Immediately following an interview, the counsellor and client independently judged each other's competence, trustworthiness, and attractiveness, and then indicated their reliance on verbal and nonverbal cues in judging these attributes. Verbal and nonverbal reliance scores were compared between the client and counsellor groups by a 2 x 3 x 2 (Group x Attribute x Reliance) analysis of variance. The results did not support the hypotheses. Both counsellors and clients appeared to rely more on verbal cues in judging competence, and on nonverbal cues in judging attractiveness and trustworthiness. Implications of the findings are discussed.